Cardiac autonomic function and oesophageal acid sensitivity in patients with non-cardiac chest pain. Issue 5 (1st November 2001) - Tougas, G; Spaziani, R; Hollerbach, S; Djuric, V; Pang, C; Upton, A R M; Fallen, E L; Kamath, M V
Abstract : BACKGROUND: Acid reflux can elicit non-cardiac chest pain (NCCP), possibly through altered visceral sensory or autonomic function. The interactions between symptoms, autonomic function, and acid exposure are poorly understood. AIM: To examine autonomic function in NCCP patients during exposure to oesophageal acid infusion. SUBJECTS AND METHODS: Autonomic activity was assessed using power spectral analysis of heart rate variability (PSHRV), before and during oesophageal acidification (0.1 N HCl), in 28 NCCP patients (40.5 (10) years; 13 females) and in 10 matched healthy controls. Measured PSHRV indices included high frequency (HF) (0.15–0.5 Hz) and low frequency (LF) (0.06–0.15 Hz) power to assess vagal and sympathetic activity, respectively. RESULTS: A total of 19/28 patients had angina-like symptoms elicited by acid. There were no significant manometric changes observed in either acid sensitive or insensitive patients. Acid sensitive patients had a higher baseline heart rate (82.9 (3.1) v 66.7 (3.5) beats/min; p<0.005) and lower baseline vagal activity (HF normalised area: 31.1 (1.9)% v 38.9 (2.3)%; p< 0.03) than acid insensitive patients. During acid infusion, vagal cardiac outflow increased (p<0.03) in acid sensitive but not in acid insensitive patients. CONCLUSIONS: Patients with angina-like pain during acid infusion have decreased resting vagal activity. The symptoms elicited by perception of acid are further associated with a simultaneous increase in vagal activity in keeping with a vagally mediated pseudoaffective response.